Respuesta :
Answer:
g(x) = -2|x+1| -3
Step-by-step explanation:
f(x) = |x|
y = f(x) + C C < 0 moves it down
y = |x| -3 for shifting down 3
y = f(x + C) C > 0 moves it left
y = |x+1| -3 for move it left 1
y = Cf(x) C > 1 stretches it in the y-direction
y = 2|x+1| -3 to stretch it 2 vertically
y = −f(x) Reflects it about x-axis
y = -2|x+1| -3
We start off with f(x) = |x|
c < 0 means move down
y = f(x) + c
3 units down
After: y = |x| - 3
c > 0 means move left
y = f(x + c)
1 unit left
After: y = |x + 1| - 3
c > 1 means y direction stretch
y = cf(x)
2 unit stretch
After: y = 2|x + 1| - 3
Reflect across x-axis can be stated as y = -f(x)
After: y = -2|x + 1| - 3
Best of Luck!